2007
DOI: 10.20396/conex.v4i1.8637961
|View full text |Cite
|
Sign up to set email alerts
|

Propuesta de intervención con jóvenes socialmente desfavorecidos a través de la actividad física y el deporte

Abstract: Uno de los nuevos retos a los que se tendrá que enfrentar la Educación Física en España y a nivel mundial son los nuevos colectivos emergentes. Dentro de este perfil de población despierta nuestro interés los denominados “jóvenes en riesgo”. En los últimos 30 años se han desarrollado diferentes programas de intervención con estas poblaciones con fines de prevención e integración y donde la actividad física y el deporte constituyen la herramienta fundamental de trabajo. Este artículo presenta la propuesta de un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 11 publications
1
3
0
8
Order By: Relevance
“…In this sense, any training done in a group and with a specific purpose in mind brings an important motivational factor (Elliot, 2000;Garet, Porter, Desimone, Birman, & Kwang, 2001), which has been stressed by teachers in other studies which have developed the MPSR in PE classes (Llopis-Goig et al, 2011;Tarín et al, 2013). Furthermore, the teachers also stressed the model's benefits for their students, improving aspects related to personal and social responsibility such as participation and effort, autonomy and respect and help for others; these results match those of other similar studies (Escartí et al, 2012;Jiménez-Martín & Durán, 2004;Sánchez-Alcaraz et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this sense, any training done in a group and with a specific purpose in mind brings an important motivational factor (Elliot, 2000;Garet, Porter, Desimone, Birman, & Kwang, 2001), which has been stressed by teachers in other studies which have developed the MPSR in PE classes (Llopis-Goig et al, 2011;Tarín et al, 2013). Furthermore, the teachers also stressed the model's benefits for their students, improving aspects related to personal and social responsibility such as participation and effort, autonomy and respect and help for others; these results match those of other similar studies (Escartí et al, 2012;Jiménez-Martín & Durán, 2004;Sánchez-Alcaraz et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Through numerous studies, different authors (Escartí et al, 2006;Jiménez-Martín & Durán, 2004;Martinek, Schilling, & Hellison, 2001;Sánchez-Alcaraz, Gómez-Mármol, Valero, & De la Cruz, 2012, 2013 have stated that by applying the MPSR, youths have developed aspects related to personal and social responsibility such as respect, self-control, self-esteem, effort, self-concept, sense of wellbeing, emotional stability, autonomy and leadership, both in PE classes and in other context, such as the family, education or sports, and at the same time they managed to decrease anxiety, depression and the perception of stress.…”
Section: Muestra Y Variablesmentioning
confidence: 99%
“…Pérez Fuentes, Gázquez, Fernández Baena y Molero (2011) abogan por la importancia de resolver las discrepancias de una manera pacífica, y conseguir, con ello, un enriquecimiento mutuo entre las personas que lo protagonizan. La resolución pacífica de los conflictos y el trabajo en valores debe considerarse como un elemento positivo en toda sociedad democrática (Davison & Wood, 2004;Jiménez Martín & Durán González, 2004;Prat, Font, Soler, & Calvo, 2004), y como parte inherente del proceso natural del desarrollo psicosocial del niño o niña (García-Hierro & Cubo Delgado, 2009).…”
Section: Introductionunclassified
“…Pérez Fuentes, Gázquez, Fernández Baena and Molero (2011) advocate for the importance of solving discrepancies peacefully and thus mutually enriching the individuals involved. Peaceful conflict resolution and work on values should be regarded as positive elements in any democratic society (Davison & Wood, 2004;Jiménez Martín & Durán González, 2004;Prat, Font, Soler, & Calvo, 2004) and as an inherent part of the child's natural psychosocial development (García-Hierro & Cubo Delgado, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Different researchers [6,9,14,15,16,17,18] have pointed through numerous researches how the implementation of PSRM has developed aspects related with Personal and Social Responsibility, like respect, self-control, selfesteem, effort, self-concept, wellness feeling, emotional stability, authonomy or leadership, at Physical Education lessons and other contexts like familiar, educative or sport [6], as well as a decrease of anxiety, depression or stress perception [5,6]. Additionally, other studies have demonstrated how, after the implementation of the model, there were significant improvements in violent and nonsportmanship behaviours [9,18].…”
Section: Introductionmentioning
confidence: 99%